Determining the Sample in Qualitative Research - Subedi, Khim Raj (Scholars' Journal, 2021)
This paper focuses on the considerations in determining the number of participants for qualitative research because of the lack of clear guidelines in this area. The study has employed a semi-systematic literature review that is embedded with the researcher's experience. The study has concluded that the purpose of the research, methodological choices, theoretical framework and analytical strategy, data saturation, researcher's knowledge and experience, and institutional and supervisor's requirements need to be considered while choosing the participants in qualitative research. In addition, the focus has been to explore in-depth information from small number of participants. Generally, participants in qualitative research can be added or removed during the research process rather than the prior determination. This paper suggests that the researchers are autonomous to select the participants in qualitative research and they can choose from a single to twenty samples that can be varied upon the depth of the information required and the nature of the inquiry. While conducting the narrative inquiry, one to twenty or more participants can be selected with justification.